3(d+6)=12(d+3)

Simple and best practice solution for 3(d+6)=12(d+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(d+6)=12(d+3) equation:


Simplifying
3(d + 6) = 12(d + 3)

Reorder the terms:
3(6 + d) = 12(d + 3)
(6 * 3 + d * 3) = 12(d + 3)
(18 + 3d) = 12(d + 3)

Reorder the terms:
18 + 3d = 12(3 + d)
18 + 3d = (3 * 12 + d * 12)
18 + 3d = (36 + 12d)

Solving
18 + 3d = 36 + 12d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-12d' to each side of the equation.
18 + 3d + -12d = 36 + 12d + -12d

Combine like terms: 3d + -12d = -9d
18 + -9d = 36 + 12d + -12d

Combine like terms: 12d + -12d = 0
18 + -9d = 36 + 0
18 + -9d = 36

Add '-18' to each side of the equation.
18 + -18 + -9d = 36 + -18

Combine like terms: 18 + -18 = 0
0 + -9d = 36 + -18
-9d = 36 + -18

Combine like terms: 36 + -18 = 18
-9d = 18

Divide each side by '-9'.
d = -2

Simplifying
d = -2

See similar equations:

| -1.3+0.4= | | 12x+20=3x+209 | | 4x+10=2(3x-11) | | 7x+21=7 | | 6z+6=2(4z-16) | | 2x^2+9x-1= | | 12-9x=74-23x | | -5x+2=2 | | 24x+(-2)=2x+3 | | (2x+1)3-(x+4)5=5-(5x+1) | | g=3+h | | 75x-5x=8x+32 | | 667=29j | | 6+4=10 | | 4z+9=45 | | f=2g | | f=29 | | 30t+42m=18600 | | 28g=-364 | | 4z+9=180 | | 27g=-364 | | x+(x+4)+3x=64 | | a+38=469 | | -(x-4)=2+6 | | y=0.6(5)+5.32 | | y=0.6(3)+5.32 | | x-2*3=12 | | z/22=25 | | 42m+30t=18600 | | 1y=0.6+5.32 | | 1=0.6+5.32 | | x^2+26x+108= |

Equations solver categories